2006
DOI: 10.1037/0021-843x.115.3.590
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory in the euthymic phase of recurrent depression.

Abstract: The authors investigated autobiographical memory specificity in subjects who formerly had depression. In 122 euthymic patients with at least two previous major depressive episodes, memory specificity was significantly impaired compared to matched control participants but not related to residual symptoms and illness characteristics, was not differentially affected by cognitive therapy, and was also not predictive of relapse/recurrence during the 2-year follow-up. However, memory specificity was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 50 publications
5
73
2
Order By: Relevance
“…This result is consistent with reports suggesting that AM performance of individuals with depression history is independent of depression status (acute episode versus remission) (Bergouignan et al, 2008;Spinhoven et al, 2006). The CAMI-SF performance was not associated with level of intellectual functioning.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with reports suggesting that AM performance of individuals with depression history is independent of depression status (acute episode versus remission) (Bergouignan et al, 2008;Spinhoven et al, 2006). The CAMI-SF performance was not associated with level of intellectual functioning.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding emotional information processing, persisting impairments have been found in the specificity of autobiographical memory [Spinhoven et al, 2006], the recognition of facial emotions [Bouhuys et al, 1999], and attentional bias [Williams et al, 1996]. Some of these impairments are also related to risk of relapse [Bouhuys et al, 1999;Williams et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…They referred to this phenomenon as overgeneral AM (OGM). A growing body of studies reported OGM as a characteristic feature in depression [18][19][20] and posttraumatic stress disorder [21] . There is also evidence for OGM in individuals with eating disorders [22] and borderline personality disorder [13,14] .…”
Section: Bipolar Disorder · Autobiographical Memory · Neuropsychologimentioning
confidence: 99%
“…Park et al [41] found a negative correlation between IQ and the number of categoric memories as one aspect of overgeneral memory retrieval in adolescents with major depressive disorder. Several studies reported a connection between age, education, and general mem-ory deficits and OGM [19,42,43] . However, Wessel et al [44] demonstrated that neuropsychological tests on semantic and episodic memory could not additionally explain variance in the prediction of OGM.…”
Section: Bipolar Disorder · Autobiographical Memory · Neuropsychologimentioning
confidence: 99%